2016
DOI: 10.1007/s12199-016-0571-x
|View full text |Cite
|
Sign up to set email alerts
|

Kampo formula “Hochu-ekki-to” suppressed carbon tetrachloride-induced hepatotoxicity in mice

Abstract: Objective The aim of this study was to investigate whether pretreatment with the Japanese herbal medicine ''Hochuekki-to'' (TJ-41) has an ameliorative effect on carbon tetrachloride (CCl 4 )-induced hepatotoxicity through anorexia prevention. Methods Twenty-four hours before CCl 4 injection, TJ-41 or saline solution was intraperitoneally administered. Furthermore, 24 h after TJ-41 injection, mice were intraperitoneally administered 1.6 g/kg CCl 4 or olive oil. Moreover, 24 h after CCl 4 /olive oil injection, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Our previous investigation found that Sasa veitchii leaf extract (SE) prevented carbon tetrachloride (CCl 4 )-induced hepatotoxicity in mice [ 12 ], suggesting that SE might maintain liver homeostasis. Although CCl 4 is commonly used in animal models to study chemical toxin-induced liver injury [ 13 , 14 ], exposure to CCl 4 does not reflect a real-life scenario. The most common etiologies of liver damage in real life are acute viral hepatitis A and B, drug-related liver injury, and the alcohol-acetaminophen syndrome (AAS).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous investigation found that Sasa veitchii leaf extract (SE) prevented carbon tetrachloride (CCl 4 )-induced hepatotoxicity in mice [ 12 ], suggesting that SE might maintain liver homeostasis. Although CCl 4 is commonly used in animal models to study chemical toxin-induced liver injury [ 13 , 14 ], exposure to CCl 4 does not reflect a real-life scenario. The most common etiologies of liver damage in real life are acute viral hepatitis A and B, drug-related liver injury, and the alcohol-acetaminophen syndrome (AAS).…”
Section: Introductionmentioning
confidence: 99%
“…Few of the authors have also used it as an acetaminophen overdose antidote examined on the mice. The induction of hepatotoxicity was made through acetaminophen single dose (750 mg / kg) (15) . Numerous treatments such as normal saline, zinc sulphate 15 or 30 mg/kg, 150 mg/kg / V-acetyl cysteine, zinc sulphate, 15 mg / kg zinc sulphate + 150 mg / kg A/-acetyl cysteine) were also administrated at the interval of one hour after the administration of overdose of acetaminophen (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities were measured using the Transaminase CII Test (Fujifilm Wako Pure Chemical) according to the manufacturer's instructions and our pre-vious studies [22][23][24]. Calibration curves were prepared using standard solutions for relative quantification.…”
Section: Plasma Biochemical Analysismentioning
confidence: 99%